Mindtoyness – zestawy dydaktyczne rozwijające zmysły i uważność poznawczą. Wykorzystanie badań ewaluacyjnych w praktyce pedagogicznej - Jolanta Kruk; Kamila Zdanowicz-Kucharczyk (Problemy Wczesnej Edukacji)
In contemporary didactic studies we find relatively little information about methods of developing mindfulness in the cognitive sphere. Our aim is to try to transfer the issues of training concentration and attention to early childhood education. The didactic and developmental benefits that can be obtained from this practice were observed during the classes with the sets. Mindtoyness – is a collection in its root referring to mindfulness – in our research project it can give teachers the tools to work on developing in-depth concentration in children.